(untitled) (International Journal of Social Science, Commerce & Management Studies, 2026)
The Goods and Services Tax (GST) is the most comprehensive tax reform in India’s post-Independent history that was implemented in the country on 1st July 2017. The main objectives of the introduction of GST were to make the complex layered tax structure, consisting of Central Excise, Service Tax, Value Added Tax (VAT) and a host of other taxes, simple and to create a simple and transparent tax regime, and to establish a single market across India. This paper aims to discuss the impact of GST on Small Business Enterprises (SBEs) which is the backbone of Indian Economy and is responsible for creating over 110 million jobs, accounting for 45% of total exports and about 30% of GDP. The study has been done through secondary data research methodology, where data has been collected from various sources such as Ministry of MSME, GST council reports, GSTIN database, RBI annual reports, NASSCOM and CII-Deloitte surveys and peer-reviewed literature from the year 2017 to 2024. Five analytical tables have been provided which covers (1) MSME registration and contribution trends; (2) Sector-wise GST compliance rate among SBEs; (3) Impact of changes in tax rate before and after GST; (4) GST related operational challenges reported by SBEs and (5) State-wise variation in GST compliance rate. The study reveals that while GST has introduced multiple long-term structural benefits like logistics cost savings, improved utilisation of input tax, enhanced formal market access, etc., small businesses are still overwhelmed with transitional and structural issues particularly in technology, working capital management, compliance burden, etc. Finally, the study recommends some policy measures to improve the GST eco-system for small businesses.